Comparative Study of Self-Compacting Concrete Containing Lightweight and Normal Aggregates - Pannem Ramamohanrao; Kumar Padmaja P. (Slovak Journal of Civil Engineering, 2019)
Based on the available literature, a simple method was adopted to calculate the packing density of aggregates and thereby reduce their void content by optimising their packing aggregates and by using two different sizes of coarse aggregates and fine aggregates. This study provides an understanding of the way in which the shape of aggregates affects the properties of self-compacting concrete (SCC). The fresh, hardened, and durable properties of SCC with normal and lightweight fly ash coarse aggregates are found at the corresponding age of the curing. Their values were compared with respect to SCC containing normal aggregates. A mix with fly ash aggregates was found to have better fresh concrete properties due to the round shape of the aggregates. After the packing of the aggregates, this mix was found to have better mechanical and durability properties than all the other concrete mixes.